Providing a Model for Implementing Knowledge Management in Supply Chain Companies (Case Study: Sazeh Gostar Saipa Company) - et. al., Tayebeh Nourali Ahari, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the current environment where markets are becoming more competitive and the rate of creativity and innovation is increasing every moment, it is vital for organizations to be aware of their knowledge and able to manage effectively this knowledge".[1] At Sazeh Gostar Saipa Company, due to the lack of collection and keeping experience in Tiba project for making the parts of this automobile by Portuguese Company Simolds, and the efforts made to improve the molds and remove their detects, the need for implementing knowledge management was formed. By providing the knowledge management model for Sazeh Gostar Saipa Company, this study attempts to present main knowledge factors in this company and by examining the required knowledge areas, the company presents the methods of developing, recording and exploiting knowledge in these areas using supervisor ideas and collecting the opinions of managers and main personnel of the company. [1] Dr. Mohsen Rasoulian